Muhammadiyah's Maqāṣid: Integrating Revelation and Science for Civilizational Resilience - Fajar Riza Ul Haq; Muhammad Amiruddin (Universitas Darussalam Gontor, 2025)
This study examined how members of Muhammadiyah, Indonesia’s largest modernist Islamic organization, interpreted and negotiated the relationship between religious authority and scientific knowledge during the COVID-19 pandemic. Drawing on a qualitative design, the analysis identified three distinct epistemological patterns—Integrative Affirmation, Puritanical Resistance, and Selective Negotiation—each shaped by the interaction of doctrinal commitments, political identity pressures, and the fragmented digital information environment. The study clarified that the notion of “Muhammadiyah’s epistemology” functions not as an attribute of an institution, but as an analytical construct that captures an institutionalized orientation toward harmonizing revelation and reason within the framework of Progressive Islam. The findings demonstrate that epistemological tendencies among members are neither uniform nor static; rather, they remain open to reinterpretation, contestation, and adjustment in response to social, political, and technological forces. Although the study offers a theoretically grounded account of epistemological dynamics within a major Muslim organization, its temporal and historical boundaries limit the assessment of long-term transformations. The article contributes to broader debates on contemporary Islamic thought by illuminating how modernist Muslim actors negotiate authority, scientific rationality, and religious authenticity under conditions of crisis and digital-era complexity.